2016
DOI: 10.1097/ico.0000000000000743
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Toxicity/Fixation Balance for Corneal Cross-Linking With Sodium Hydroxymethylglycinate (SMG) and Riboflavin-UVA (CXL) in an Ex Vivo Rabbit Model Using Confocal Laser Scanning Fluorescence Microscopy

Abstract: Purpose To develop methods to delineate the relationship between endothelial cell toxicity and tissue fixation (toxicity/fixation) using sodium hydroxymethylglycinate (SMG), a formaldehyde releaser, and riboflavin-UVA (CXL) for therapeutic tissue cross-linking of the cornea. Methods Eleven (11) fresh cadaveric rabbit heads were used for ex vivo corneal cross-linking simulation. Following epithelial debridement, the tissue was exposed to 1/4 Max (9.765mM) or 1/3Max (13.02mM) SMG at pH 8.5 for 30min or ribofla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…The previous experiments indicated that a concentration-dependent crosslinking effect could be obtained using SMG, with effects ranging well above those achieved with standard CXL as determined by thermal analysis. 14 …”
mentioning
confidence: 99%
“…The previous experiments indicated that a concentration-dependent crosslinking effect could be obtained using SMG, with effects ranging well above those achieved with standard CXL as determined by thermal analysis. 14 …”
mentioning
confidence: 99%
“…119,120 UV-A use with scleral CXL has been associated with decreased dark-adapted ERG amplitudes up to 3 months posttreatment, with apoptotic cells and ultrastructural changes in retina layers also found. 121 111,118,119,[122][123][124][125][126][127][128][129][130] Glyceraldehyde is a non-light-activated chemical shown to increase scleral rigidity, but has ill effects on the neighboring cornea and muscles. 120 Alternatively, topical beta-nitroalcohols (or ''BNAs,'' commonly found in antibiotics and shampoos) and formaldehyde releasers (or ''FARs,'' which are preservatives found in cosmetics, body wash, and ophthalmic solutions; e.g., BLU Gel A multidose artificial tears, SOOFT italia [Montegiorgio FM, Italy]) effectively crosslink corneal and scleral collagen in vitro, and have very good safety profiles (Hoang Q, et al IOVS 2013;54:ARVO E-Abstract 136).…”
Section: Solution 3: Advanced Stage Disease Interventions: Current Anmentioning
confidence: 99%
“…120 Alternatively, topical beta-nitroalcohols (or ''BNAs,'' commonly found in antibiotics and shampoos) and formaldehyde releasers (or ''FARs,'' which are preservatives found in cosmetics, body wash, and ophthalmic solutions; e.g., BLU Gel A multidose artificial tears, SOOFT italia [Montegiorgio FM, Italy]) effectively crosslink corneal and scleral collagen in vitro, and have very good safety profiles (Hoang Q, et al IOVS 2013;54:ARVO E-Abstract 136). [122][123][124][125][126][127] Specifically, in a comparative toxicity study of nine topical crosslinking agents in four different cell lines with a semiquantitative analysis using five categories of toxicity/fixation (Hoang Q, et al IOVS 2013;54:ARVO E-Abstract 136), the toxicity levels varied by a factor of 10 3 , with the least toxic being mononitroalcohol BNAs, and genipin among the most relatively toxic. 122 Ultimately, regardless of the scleral reinforcement approach used, it is paramount to detect scleral weakness before staphyloma formation, to determine which highly myopic eyes are headed down the path toward staphyloma and MMD formation.…”
Section: Solution 3: Advanced Stage Disease Interventions: Current Anmentioning
confidence: 99%
“…The formulation contained various concentrations of 15cP HPMC, while keeping the final SMG concentration at 10 mM and NaHCO 3 at 100 mM. The concentration of 10 mM SMG was chosen based on the results from a previous rabbit cornea study in which this concentration was determined to be effective yet non-toxic [19]. Each formulation was prepared freshly on the day of the experiment.…”
Section: Tissue Cross-linkingmentioning
confidence: 99%
“…Less stable fibrils will result in a lower T m and likewise, more stable fibrils induced by the cross-linking treatment will raise the T m . T m has been used as a surrogate assay for tissue cross-linking efficacy, in lieu of mechanical testing, for many decades in the biomaterials world and we have applied to this simple and efficient technique to our therapeutic tissue cross-linking studies previously [19].…”
Section: Differential Scanning Calorimetry (Dsc)mentioning
confidence: 99%